Inhibition of Matrix Metalloproteinase with BB-94 Protects against Caerulein-Induced Pancreatitis via Modulating Neutrophil and Macrophage Activation - Zengkai Wu; Tunike Mulatibieke; Mengya Niu; Bin Li; Juanjuan Dai; Xin Ye; Yan He; Congying Chen; Li Wen; Guoyong Hu (Gastroenterology Research and Practice)
Background/Objective. Inhibition of matrix metalloproteinases (MMPs), particularly MMP-9, attenuates leukocyte infiltration and pancreatic and distant organ damages in acute pancreatitis (AP). However, it is unclear whether MMPs mediate inflammatory cell activation. In this study, we investigated the effects of inhibition of MMPs on neutrophil and macrophage activation in caerulein-induced pancreatitis. Methods. AP was induced in Balb/C mice by ten hourly intraperitoneal injections of caerulein (100 μg/kg) and LPS (5 mg/kg). The MMP inhibitor, BB-94 (20 mg/kg) was intraperitoneally administered 30 min before AP induction. Pancreatitis was confirmed by histology and serum amylase and lipase. Expression of pancreatic proinflammatory mediators and NF-κB activation were assessed. Bone marrow-derived neutrophils (BMDNs) and macrophages (BMDMs) were isolated. BMDNs were activated by phorbol 12-myristate 13-acetate (PMA, 50 ng/ml) and neutrophil reactive oxygen species (ROS) production was recorded. BMDMs were stimulated with 10 ng/ml IFN-γ and 100 ng/ml LPS to induce M1 macrophage polarization. Results. Pancreatic MMP-9 was markedly upregulated and serum MMP-9 was increased in caerulein-induced pancreatitis. Inhibition of MMP with BB-94 ameliorated pancreatic tissue damage and decreased the expression of proinflammatory cytokines (TNFα and IL-6) or chemokines (CCL2 and CXCL2) and NF-κB activation. Furthermore, using isolated BMDNs and BMDMs, we found that inhibition of MMP with BB-94 markedly decreased neutrophil ROS production, inhibited inflammatory macrophage polarization and NF-κB activation. Conclusions. Our results showed that inhibition of MMP with BB-94 protected against pancreatic inflammatory responses in caerulein-induced pancreatitis via modulating neutrophil and macrophage activation.